2017
DOI: 10.29063/ajrh2017/v21i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Violence among Married Women in Debre Tabor Town, Northwest Ethiopia: A Qualitative Study

Abstract: Gender-based violence is one of the major public health problems in Ethiopia. This study aimed to assess the perception and attitude of the community towards gender-based violence among married women in Northwest Ethiopia. A qualitative study was conducted using the purposive sampling technique for the three focus group discussions and ten in-depth interviews among married women. Data was analyzed thematically using version 3.4 of the Open Code Software. Most of the participants perceived that gender-based vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 20 publications
9
24
0
1
Order By: Relevance
“…Many victims of housemaids reported that when the employers took excess alcohol than usual, they assaulted the housemaids. A qualitative study in Debre Tabor town also supported this finding [24]. is is because alcohol has a depressive mental impairment and thus, human beings are encouraged to undertake violence.…”
Section: Discussionmentioning
confidence: 77%
“…Many victims of housemaids reported that when the employers took excess alcohol than usual, they assaulted the housemaids. A qualitative study in Debre Tabor town also supported this finding [24]. is is because alcohol has a depressive mental impairment and thus, human beings are encouraged to undertake violence.…”
Section: Discussionmentioning
confidence: 77%
“…Consistent with the Connell’s theory of gender and power, social constructs, including the sexual division of labour, power and social norms, conflict/violence in marriage is taken for granted, and women are expected to be tolerant and sacrificial [30,31], enforcing the tendency to preserve women’s subordination. Other studies also confirm the gender inequitable norms and practices linked to IPV [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmada, ayrıca aile içi şiddetin yaygın olduğu, bireylerin tutumunun ve geleneksel normların cinsiyet temelli şiddetin evli kadınlar üzerindeki kabul edilebilirliğini belirlemede önemli rol oynadığı belirlenmiştir. 18 Nijerya'da, kırsal kesimdeki 15-49 yaş grubunda 3911 kadın ile rastgele örneklem kullanılarak yapılan araştırmada da, kadınların eş şiddetine yönelik tutumlarında sosyo-ekonomik dezavantajların yanı sıra; sosyal, ekonomik, dini ve kültürel faktörlerin etkili olduğu belirtilmiştir. 19 Çoklu gösterge küme araştırması verileri kullanılarak, 15-49 yaş aralığındaki Vietnamlı kadınlarda aile içi şiddeti destekleyici tutumlara katkıda bulunan sosyoekonomik faktörleri tanımlamak amacı ile yapılan bir çalışmada, aile içi şiddeti kabul etme yaygınlığının 2006-2011 yılları arasında azaldığı (%65,1'den %36,1'e düşmüştür) bildirilmiştir.…”
Section: Kullanılan Araçlarunclassified